ADAT PERKAWINAN SUKU BAJO DI DESA SAINOA KECAMATAN BUNGKU SELATAN KABUPATEN MOROWALI: 1976-2017 - Ratna Ratna; La Ode Ali Basri, Basrin Melamba (Jurusan Ilmu Sejarah Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
This study aims to describe the Bajo tribal marriages at Sainoa Village, Bungku Selatan District, Morowali Regency: 1976-2017. The method used in this study was the historical method refers to the following steps: (1) Selection of topics, (2) Collection of sources, (3) Verification (historical criticism and validity of sources), (4) Interpretation (interpretation: analysis and synthesis), and (5) Historiography (writing). The results showed that: 1) The process of implementing Bajo tribal marriages at Sainoa Village was carried out through several stages namely; a) mate selection, b) assessment (tilau talang). c) hosting (Massuro). d) submission of marriage costs (nyoroh), e) pabarraang (girlfriend's night), f) marriage contract (panic). Marriage contract is held in lammeh (bridal house). 2) Customary equipment in the process of marriage, namely betel leaf, areca nut, lime, dalah kuneh, candles, flags and oje '. 3) The meaning contained in the marriage customs appears in the traditional equipment that accompanies the implementation of the marriage stages. They were consisted of betel leaf, areca nut, lime, dalah yellow, wax, flag and oje ’. All of these objects have meaning so that the bride and groom's life journey always gets blessings from the Almighty. 4) Changes in customary marriage appeared in the process and equipment that follows along with the times. Keyword: Bajo, Marriage, Custom, Symbolic Meaning